Agronomic biofortification with selenium impacts storage proteins in grains of upland rice - Reis, Heitor Pontes Gestal [UNESP]; de Queiroz Barcelos, Jéssica Pigatto [UNESP]; Silva, Vinícius Martins [UNESP]; Santos, Elcio Ferreira; Tavanti, Renan Francisco Rimoldi [UNESP]; Putti, Fernando Ferrari [UNESP]; Young, Scott D; Broadley, Martin R; White, Philip J; dos Reis, André Rodrigues [UNESP] (Wiley, 2020)
BACKGROUND: Selenium (Se) is an essential element for humans and animals. Rice is one of the most commonly consumed cereals in the world, so the agronomic biofortification of cereals with Se may be a good strategy to increase the levels of daily intake of Se by the population. This study evaluated the agronomic biofortification of rice genotypes with Se and its effects on grain nutritional quality. Five rates of Se (0, 10, 25, 50, and 100 g ha−1) were applied as selenate via the soil to three rice genotypes under field conditions. RESULTS: Selenium concentrations in the leaves and polished grains increased linearly in response to Se application rates. A highly significant correlation was observed between the Se rates and the Se concentration in the leaves and grains, indicating high translocation of Se. The application of Se also increased the concentration of albumin, globulin, prolamin, and glutelin in polished grains. CONCLUSION: Biofortifying rice genotypes using 25 g Se ha−1 could increase the average daily Se intake from 4.64 to 66 μg day−1. Considering that the recommended daily intake of Se by adults is 55 μg day−1, this agronomic strategy could contribute to alleviating widespread Se malnutrition. © 2019 Society of Chemical Industry.
Keywords: biofortification; micronutrients; rice (Oryza sativa L.); seed proteins; selenium